The social dynamics of law : an inquiry into the multiformity of law in contemporary Malaysia / Mohd Darbi Hashim - Hashim, Mohd Darbi (Faculty of Administratron and Law, 2004)
Browsing randomly through the local newspapers over the last four or five months a newspaper reader would invariably stumble upon the news headlines and reports on the various state legislative and quasi-legislative actions as well as law enforcement measures in this country such as follows.